August Aichhorn papers - Aichhorn, August, 1878-1949.
Correspondence with Otto Fleischmann, Hans Lampl, Jeanne Lampl-de Groot, and others; transcripts of lectures delivered by Aichhorn, Anna Freud, and Kate Friedlander at a conference in Lausanne, Switzerland, in 1948; bibliographies of Aichhorn's published writings; and an article written by Aichhorn, 1901.
Photocopies and transcripts, in part.
Psychoanalyst.
Collection material in German.
Forms part of: Sigmund Freud collection.
Keywords: Fleischmann, Otto, -- 1896-1963 -- Correspondence; Freud, Anna, -- 1895-1982.; Friedlander, Kate; Lampl, Hans -- Correspondence; Lampl-de Groot, Jeanne -- Correspondence; Psychoanalysis; Psychoanalysts